Service System Innovation and Competitiveness In an Emerging Market: The Moderating Role of Managerial Competencies - AKPAN, EKOM ETIM; Igwe, Anthony Aniagbaoso; Sylva, Waribugo; Udoh, Ben Etim (Gadjah Mada International Journal of Business, 2024)
This study empirically examines the correlation between service system innovation and competitiveness in Nigeria, an emerging market, by focusing on the country’s mobile telecommunications sector. The moderating effect of managerial competencies was also tested. Due to the contribution of the telecommunications sector to the economic well-being of Nigeria and the world’s economy at large, the sector witnesses a high level of competition among its players, resulting in unsustainable price wars, negatively impacting the telecommunication firms and their ability to invest in service improvements. Thus, there is a need for a study into the factors affecting competitiveness in the telecommunications sector. A cross sectional survey was used because the study explored the relationships between service system innovation, managerial competencies and competitiveness. The study used a survey instrument, which was sent to 450 respondents using Google Forms, out of which 230 responded. The 230 returned copies represented a 51.1 percent return rate, which satisfied the minimum required return rate for a cross sectional study. The study’s hypotheses were tested using the partial least squares structural equation model (PLS-SEM). The finding revealed that service system innovation (idea development, service development and commercialization) enhances the competitiveness of mobile telecommunication firms. Thus, an increase in idea development, service development and commercialization is essential for a competitive advantage. Also, managerial competencies were found to significantly moderate the relationship between service system innovation and competitiveness. The study provides a new insight into how service system innovation affects the competitiveness of telecommunications companies, particularly in emerging markets, with Nigeria as the focal point. It also shows the role managerial competencies play in the telecommunications sector. This study offers proof of the traits of service system innovation, managerial competencies, and competitiveness in the telecommunications sector. It also developed and tested a scale for measuring these variables, which future studies could adopt.